Biofaciological zonation of benthic foraminifera of the continental shelf of Campos Basin, SE Brazil - Vieira, Fabiana Silva; Koutsoukos, Eduardo A. M. (Quaternary international, 2015)
Data on the microbiofaciological zonation of benthic foraminifera were obtained from 82 sub-samples from the subsurface sediments of the continental shelf of Campos Basin, in southeastern Brazil. The abundance and distribution of the 93 species identified during the study were related to depth and temperature of the water, as well as to sediment grain size. Four biofacies were established: biofacies I, represented by the sandier coastal sediments and dominated by Pseudononion atlanticum and miliolids; biofacies II, associated with carbonated substrates, and represented by Amphistegina lessonii and miliolids; biofacies III, represented by mini-cores A2, where Bulimina marginata is predominant in all the samples; and biofacies IV, associated with the muddy substrates of the outer continental shelf, dominated by B. marginata, Discorbis orbicularis and Globocassidulina subglobosa. In general, the miliolids were more abundant in sandy sediments (except A2), while the bolivinids and buliminids predominated in the sediments with a silt fraction, which were normally associated with higher levels of organic matter. The highest species diversity and equitability, and lowest dominance indices were recorded in the sandy sediments, whereas the silty sediments were characterized by a predominance of opportunists such as Bolivina spp. and Bulimina spp. Species that were abundant in one stratum of a mini-core tended to be abundant throughout the core, indicating stable conditions over long periods, which guaranteed the settlement of these species.